SOA/SPD-based incoherent SAC-OCDMA system at 9×5Gbps - Al-Khafaji, Hamza M. R.; Aljunid, S. A.; Amphawan, Angela; Fadhil, Hilal A. (The Institute of Electronics, Information and Communication Engineers, 2013)
To boost the performance of spectral-amplitude coding optical code-division multiple-access (SAC-OCDMA) systems, the need for an effective solution to diminish phase-induced intensity noise (PIIN) is becoming progressively more crucial. In this letter, two PIIN suppression approaches: semiconductor optical amplifier (SOA)-based noise cleaning, and single photodiode detection (SPD) are employed. The performance of the hybrid SOA/SPD scheme is validated through simulation experiments. Our results show that SOA/SPD scheme remarkably improves the performance and increases the throughput of SAC-OCDMA system.